2022
DOI: 10.1186/s13568-022-01407-9
|View full text |Cite|
|
Sign up to set email alerts
|

Alternative use of phage display: phage M13 can remain viable in the intestines of poultry without causing damage

Abstract: Phage display (PD) is a tool for developing new molecules to control pathogens. Peptides selected by PD are commonly synthesised and tested, but the use of phage M13 displaying the selected peptides as a direct biding in the intestinal tract has not yet been tested. This study evaluated whether phage M13 can remain viable in the chicken gastrointestinal tract and whether it causes injury or humoral immune response. We inoculated phage M13 or E. coli ER2738 (ECR) infected with M13 into birds at different ages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Following publication of the original article (Santos et al 2022 ), the authors reported an error in the first author’s name “Fabiana de Almeida Araújo Santos”. The given name should be “Fabiana de Almeida Araújo” and last name is “Santos”.…”
Section: Correction To: Amb Express (2022) 12:64 Https://do...mentioning
confidence: 99%
“…Following publication of the original article (Santos et al 2022 ), the authors reported an error in the first author’s name “Fabiana de Almeida Araújo Santos”. The given name should be “Fabiana de Almeida Araújo” and last name is “Santos”.…”
Section: Correction To: Amb Express (2022) 12:64 Https://do...mentioning
confidence: 99%